Demographic conditioning of awareness of prophylaxis against Streptococcus agalactiae (GBS) infections among parturients - Bąk, Beata; Sikorski, Marek; Woźniak, Aleksandra (Medical Studies/Studia Medyczne, 2016)
Introduction: Infection with Streptococcus agalactiae (group B Streptococcus – GBS) is a frequent cause of serious complications in the neonatal period. Circa 10–30% of pregnant women are carriers of this streptococcus. Current prophylaxis of GBS infections is an elementary way of defining whether there is a risk of the child’s infection. The achieved research result determines further perinatal proceedings. Aim of the research: To determine how such factors as age, residence, education, and current women’s parity influence their awareness concerning prophylaxis of infections with Streptococcus agalactiae. The research also analysed women’s knowledge of threats to their health related to the presence of GBS infections. Material and methods : Analysis of 164 author’s questionnaires completed by women giving birth at the labour ward in the early delivery stage. The results were analysed in view of statistical accordance of measurable qualities by means of c2 test. For statistical conclusions, the significance level of p < 0.05 was adopted. Results and conclusions: Older pregnant women in comparison with the younger ones more frequently realise the importance of the GBS prophylaxis. Women from the urban environment have greater awareness of the GBS prophylaxis than women from the rural environment. An increase in the level of education is related to an increase in the GBS prophylaxis awareness. Women in their first pregnancy have a greater knowledge of the standards of pregnancy proceedings connected with GBS than women who have already given birth to a child.